2005
DOI: 10.1097/01.yco.0000165590.68058.b0
|View full text |Cite
|
Sign up to set email alerts
|

Understanding alcohol misuse and comorbid psychiatric disorders

Abstract: Depression in patients with alcohol use disorders cannot be ignored. Treatment of depression alone will not help the alcohol use problems. All psychiatric inpatients should be screened for alcohol use disorders as part of their risk assessment. Research is focusing more on examining the complexities of these disorders, but there are no specific pharmacotherapies to treat particular comorbid conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
2

Year Published

2008
2008
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 31 publications
2
15
0
2
Order By: Relevance
“…While these symptoms are among the more common postpartum symptoms, they are elevated in this high-risk sample compared to national average rates of 10-12% for depression and 5.5-17% for psychotic symptoms. In addition the findings are also consistent with other studies that have found an association of depression and anxiety with alcohol use among lower risk obstetric samples (Baigent 2005). There is also considerable research which shows an association of lower cognitive abilities with higher rates of depression, anxiety and overall psychological distress (Zammit et al 2004), similar to the findings of this study.…”
Section: Discussionsupporting
confidence: 82%
“…While these symptoms are among the more common postpartum symptoms, they are elevated in this high-risk sample compared to national average rates of 10-12% for depression and 5.5-17% for psychotic symptoms. In addition the findings are also consistent with other studies that have found an association of depression and anxiety with alcohol use among lower risk obstetric samples (Baigent 2005). There is also considerable research which shows an association of lower cognitive abilities with higher rates of depression, anxiety and overall psychological distress (Zammit et al 2004), similar to the findings of this study.…”
Section: Discussionsupporting
confidence: 82%
“…Although these symptoms may reduce during sobriety, data appear to indicate that a protracted withdrawal syndrome, including anxiety and depressive symptoms, may develop following acute alcohol withdrawal and may persist for at least 1 year [12]. It was suggested to treat these symptoms with antidepressants, especially if they are still present after 1 week of abstinence [11].…”
Section: Introductionmentioning
confidence: 98%
“…These symptoms often are observed in patients who are intoxicated or undergoing alcohol detoxification and they commonly emerge during alcohol withdrawal [12]. Usually, anxiety and depressive symptoms will disappear with the alcohol withdrawal treatment, without the need of extra treatment for these symptoms [11,13]. Although these symptoms may reduce during sobriety, data appear to indicate that a protracted withdrawal syndrome, including anxiety and depressive symptoms, may develop following acute alcohol withdrawal and may persist for at least 1 year [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por outro, eles apontaram que as intervenções padronizadas, consideradas "padrão ouro", ou seja, amostragem randômica e controlada, (Brasiliano, Hochgraf, 2005b). Em segundo lugar é preciso ressaltar que vários autores têm sustentado a importância da avaliação de transtornos psiquiátricos subclínicos (Lewinsohn et al, 2004;Baigent, 2005). Com relação aos transtornos alimentares, as síndromes alimentares parciais ou subclínicas estão associadas a significativas taxas de comorbidade com outros transtornos psiquiátricos, risco considerável de suicídio e índices elevados de prejuízo no funcionamento psicológico e social (Lewinsohn et al, 2000a).…”
Section: Evolução Em Tratamentounclassified